Knowledge and attitudes about emergency contraception among pharmacist and physician preceptors in South Carolina - Sarah Shrader; Ann M Rodden; Lisa Carroll; et al (Dove Medical Press, 2010)
Sarah Shrader1,2, Ann M Rodden1, Lisa Carroll3, Lars E Peterson11Medical University of South Carolina, Department of Family Medicine, Charleston, SC, USA; 2South Carolina College of Pharmacy, Department of Clinical Pharmacy and Outcomes Sciences, Charleston, SC, USA; 3Spartanburg Regional Family Medicine Residency Program, Department of Family Medicine, Spartanburg, SC, USABackground: Emergency contraception (EC) may reduce unintended pregnancies if patients are informed and have access. A great deal of medical education occurs during medical and pharmacy training community clerkships. This study concurrently assesses knowledge and attitudes about EC between community physician and pharmacist preceptors who prescribe/dispense EC.Study design: Electronic survey of demographic information, knowledge-based, and attitude questions related to EC was completed by 182 (36.6% response rate) South Carolina community physicians and pharmacists who precept students. Comparisons were performed using chi-square or Fischer’s exact test.Results: In the study population, approximately 62% of pharmacists dispense EC while only 28% of physicians prescribe it. More physicians than pharmacists believe repetitive use is not harmful (48.3% vs 28.0%, P = 0.010), while more pharmacists believe it causes birth defects (22.6% vs 7.9%, P = 0.008).Conclusion: Overall, both physicians and pharmacists have poor knowledge about EC. Further education for both groups may be needed so future physicians and pharmacists are not taught incorrectly during their training and so patient access is not hampered by prescriber misunderstanding.Keywords: emergency contraception, levonorgestrel, pharmacist, physician